Extracorporeal blood purification in patients with liver failure: Considerations for the low-and-middle income countries of Latin America - Villanueva, Vladimir Barrera; Barrera Amorós, Daniel Alejandro; Castillo Echeverria, Eira Ingrid; Budar-Fernández, Luis F.; Salas Nolasco, Omar Israel; Juncos, Luis A.; Rizo-Topete, Lilia (Frontiers in Nephrology, 2023)
Acute liver failure (ALF) is a syndrome characterized by an acute alteration of liver blood tests, in a patient without underlying chronic liver disease. When these biochemical features appear in conjunction with altered mental status in a patient known to have chronic liver disease, it is called acute on chronic liver failure (ACLF). Liver failure in both scenarios can develop a spectrum of extrarenal indications to start the continuous renal replacement therapy (CRRT). Hyponatremia is the most frequent electrolyte imbalance, in conjunction with hyperammonemia and the consequent brain edema constitutes an indication of CRRT. (Figure 1). In addition, acute kidney injury (AKI) is frequent on ALF, as critical care nephrologists, we can offer an approach to critically ill patients who requires support for the most frequent causes of mortality: hepatic encephalopathy (HE) and AKI. Besides, liver transplantation is the only curative therapeutic option for both (ALF and ACLF), we should keep in mind that extracorporeal liver assist devices (ELAD) are conceived to give support as a bridge- to- transplantation or bridge-to-recovery therapy. Currently, ELAD are classified as artificial or bioartificial devices. Bioartificial devices are considered out of the scope of this review. Focusing on artificial ELAD devices we can classify them by their kinetics remotion: diffusive and absorptive, diffusive, plasma-filtration and coupled plasma-filtration and separation. In this review we aim to provide critical care nephrologists a new perspective focusing on ELAD that can be performed with a single third-generation CRRT machine, offering new insight into extrarenal CRRT indications.